Literasi keuangan dan kepercayaan sebagai determinan adopsi dompet digital: Studi pada pengguna Shopeepay di kalangan mahasiswa pendidikan ekonomi - Nenden Susilowati; Sabrina Alisa Febriyanti; Axelina Dava Avrielliandiny; Puspita Tyas Shabrina; Angga Revaldo (Nur Science Institute, 2025)
The development of digital financial services has changed people's transaction patterns, including among university students. ShopeePay, a popular digital wallet, offers convenience, speed, and secure transactions. However, students' decisions to use it are influenced not only by technical aspects but also by financial literacy and trust levels. This study aims to analyze the influence of financial literacy and trust on the decision to use ShopeePay among Economics Education students using a quantitative approach through a questionnaire survey. The sample for this study consisted of students selected using a proportional random sampling technique. Data were analyzed using validity and reliability tests, classical assumption tests, and multiple regression. The results showed that all variables were valid and reliable, that the regression model met the classical assumption tests, and that financial literacy and trust had a positive and significant effect on the decision to use ShopeePay. Thus, the higher the students' financial literacy and the stronger their trust in ShopeePay, the greater their tendency to use the service. This study suggests that improving financial literacy and strengthening security and trust are important factors in encouraging university students to use digital wallets.